Structurally Reinforced Silicon/Graphene Composite for Lithium‐Ion Battery Anodes: Carbon Anchor as a Conductive Structural Support. Issue 6 (10th February 2022) - Hoon Park, Byung; Yang, Hanmo; Gil Choi, Yong; Kim, Kwang‐Bum
Abstract: Herein, a Si/reduced graphene oxide (rGO)/C microsphere composite is reported, wherein sucrose‐derived carbon binds Si nanoparticles (NPs) and rGO to act as a carbon anchor and links neighboring rGO sheets to reinforce the composite structure. In this structurally reinforced Si/rGO/C composite, the electron conduction pathways between rGO and Si NPs were maintained even under large volume changes during repeated charge–discharge processes. Consequently, the Si/rGO/C composite anode exhibited an initial discharge capacity of 1209 mAh g −1 and superior cyclability (92 % retention at 100 cycles), initial coulombic efficiency of 80.5 %, and high‐rate capability even at a high C rate (6 C). Furthermore, the change in anode thickness after repeated cycling was negligible, confirming the structural stability imparted by the sucrose‐derived carbon binder. A full cell assembled with a LiCoO2 cathode and the Si/rGO/C composite anode remained stable over 200 cycles. Abstract : Anchor in : The figure illustrates the charge/discharge behavior of the silicon/carbon composite and shows full cell cycling. With a conductive carbon anchor, a robust structure is realized under conditions of repeated volume changes of silicon. This results in a reversible charge/discharge process. It demonstrates that a conductive structural supporter should be used to achieve stable cyclability of the silicon/carbon composite anode.